Magnetic resonance based morphometric analysis of the tentorial notch - Arrambide Garza, Francisco Javier; De la Garza Castro, Oscar; Alvarez Lozada, L. A.; Carranza Rodríguez, Erick; Quiroga Garza, Alejandro; Gómez Sánchez, Arnulfo; Pinales Razo, R.; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (Polish Anatomical Society, 2023)
Background: The study of the tentorial notch can improve the understanding of brain injury mechanisms. Tentorial morphology has been analysed primarily in cadaveric studies. However, the postmortem effect can cause variability in the measurements. The objective was to evaluate the morphometry of the tentorial notch and the third cranial nerve on living subjects using magnetic resonance imaging (MRI). Materials and methods: A retrospective cross-sectional study was performed. Using consecutive cases, 60 MRI scans were analysed for tentorial notch morphology. Maximum notch width (MNW), notch length (NL), interpedunculoclival (IC) distance, apicotectal (AT) distance, third cranial nerve (CN-III) distance, and interCN-III angle, were obtained. For the classification of the tentorial notch quartile distribution technique for MNW, NL, AT distance, and IC distance were used. Results: According to the quartile of the MNW, patients were stratified into narrow, midrange, and wide groups. Using the NL quartile groups, they were also classified as short, midrange, and long. With these, the tentorial notch could be classified into eight types. Statistical differences between genders in the MNW and inter-CN-III angle were found, as well as a strong positive correlation between NL and AT distance, and between right and left CN-III distances. Conclusions: There were differences between the cadaveric samples and living subjects in the CN-III distances. This difference could be explained by the dehydration of brain volume in the postmortem process which may cause nerve elongation. Morphometry of the tentorial notch and its neurovascular relations allows a better understanding of the mechanisms of brain herniation. (Folia Morphol 2023; 82, 4: 784–790)